Pengembangan Alat Peraga Sistem Tata Surya Bagi Siswa Tunanetra di SLB-A Yaat Klaten Kelas IX - Elliza Efina Rahmawati Putri; Winarti Winarti (PLD UIN Sunan Kalijaga, 2014)
Blind students have restrictiveness on their sight so it is difficult for them to know solar system concepts which demand a visual role actively. Based on this reality, the innovation of solar system props that was designed specifically for blind students is needed. This research purposes are: (1) developing solar system props as a physics learning media for students of SLB-A YAAT on 9th grade, (2) knowing the quality of solar system props as a physics learning media, (3) knowing the quality of solar system material recording as a physics learning media, and (4) knowing blind students response toward solar system props and material recording as a learning media for solar system material.This research is R & D with 4-D model according to Thiagarajan, Semmel, and Semmel that was confined to extent test in Develop step. The research was done in SLB-A YAAT Klaten. Testing subject on this research are 3 students of 9th grade on limit test and 4 students of 9th grade on extent test. Instrument of data collection in this research are instrument and product validation sheet, product quality appraisal sheet for material expert, media expert, and SLB-A YAAT physics teacher by using Likert scale in checklist. Instrument for students is students response questionnaire by using Guttman scale in checklist. Analyzing data technique that was used in this research is descriptive quantitative.Based on appraisal of media expert, the props and material recording have Very Good quality with percentage 87,50% and 86,67%.Whereas appraisal of material expert has Very Good quality with percentage 87,50% and 82,35%. Appraisal of SLB-A YAAT physics teacher has Very Good quality with percentage 90,27% and 81,52%. The result of students response on limit test for the props and material recording are Very Good with percentage 95,24% and 100%. On extent test, the response is Very Good with percentage 92,86% and 100%.